GreenLight Laser photoselective vapo-enucleation of the prostate with front-firing emission versus plasmakinetic resection of the prostate for benign prostate hyperplasia - Cheng, Xiangming (Transl Androl Urol, 2020)
BACKGROUND: Although the conventional, monopolar transurethral resection of the prostate (TURP) has proven to be an effective and relatively safe treatment for patients with benign prostatic hyperplasia (BPH), many new endoscopic technologies have been introduced to treat BPH. With the development of laser, there are several alternative transurethral procedures embracing laser therapies. Herein, this study sought to explore the efficacy, safety and follow-up of GreenLight laser photoselective vapo-enucleation of the prostate (PVEP) with front-firing emission compared with plasmakinetic resection of the prostate (PKRP) used to surgically manage BPH. METHODS: Data from patients who underwent either GreenLight laser PVEP or PKRP were retrospectively collected from March 2013 to May 2018. Perioperative data from both groups were compared. RESULTS: Totally, 43 and 45 patients were included in the PVEP and PKRP groups, respectively. No significant difference was observed in excision efficiency ratio (resected prostate weight/operation time) between the two groups (P=0.372). The efficiency ratio of the first 20 PVEP procedures (0.36±0.09 g/min) was significantly lower than that of the second 23 PVEP procedures (0.45±0.18 g/min) (P=0.042). The PVEP group experienced a shorter duration of catheterization, postoperative hospital stay and irrigation time than the PKRP group (P<0.001, P=0.001 and P<0.001, respectively). There was no statistically significant difference between the two groups (P=0.937) in terms of overall postoperative complications. Three months after surgery, the international prostate symptoms (IPSS) score, quality of life (QOL) score, postvoid residual (PVR) volume and maximum urinary flow rate (Q(max)) were decreased in both groups (P<0.001 for all) and were comparable between both groups (P=0.635, 0.662, 0.671 and 0.924, respectively). CONCLUSIONS: GreenLight laser PVEP with front-firing emission was safe and effective modality in treating patients with BPH with short-term follow-up. PVEP was associated with shorter catheterization and postoperative hospital stay time compared with PKRP.